Variability of the modified Balance Error Scoring System at baseline using objective and subjective balance measures - Amaal J Starling; Danielle F Leong; Jamie M Bogle; Bert B Vargas (Concussion)
Aim: To investigate preseason modified Balance Error Scoring System (mBESS) performance in a collegiate football cohort; to compare scores to an objective mobile balance measurement tool. Materials...